Sluicing cross-linguistic perspectives - Merchant, Jason; Simpson, Andrew, 1962- (Oxford : Oxford University Press, 2012)
This volume expands our current understanding of the ways in which languages allow for ellipsis of the sluicing type to occur, and shows how sluicing constructions reveal important information about the general architecture of grammar.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Ellipsis